Effect of Forest Species on the Productivity of Groundstorey Crops - Saroj, P. L.; Dwivedi, V. K.; Kumar, Ashok; Dadhwal, K. S. (Indian Forester, 1999)
The investigation was carried out at CSWCRTI, Research Farm, Selakui, Dehra Dun to see the productivity of groundstorey crops with different tree species. The cropping sequence (jowar-toria) was tested wi th three plantations i.e. Eucalyptus hybrid, Bombax ceiba and mixed plantations (natural) of Cassia jistula, Bombax ceiba, Acacia catechu, Lannea coromandalica and Dalbergia sissoo. It was observed that about 14.89, 12.79 and 12.14 tlha green fodder yield of jowar can be obtained with Bombax ceiba, Eucalyptus hybrid and mixed plantations, respectively. The trend was same with toria and seed yield recorded were 3.68, 2.78 and 2.38 q/ha under Bombax ceiba, Eucalyptus hybrid and mixed plantations, respectively. The yield of both the crops increases with increasiug distance from the tree trunk, however the direction did not influence the yield of groundstorey crops.